87.6k views
3 votes
A student is trying to solve the system of two equations given below:

Equation P: y + z = 6
Equation Q: 3y + 4z = 1

Which of the following is a possible step used in eliminating the y-term?
(y + z = 6) ⋅ 4
(3y + 4z = 1) ⋅ 4
(y + z = 6) ⋅ −3
(3y + 4z = 1) ⋅ 3

User Cosmitar
by
5.8k points

2 Answers

1 vote
(y+z=6) • -3 so you cancel out the 3's if you add
User Rjbs
by
5.6k points
1 vote
(y+z=6)* -3

Then you can subtract it from 3y+4z=1 and cancel out the y variable.
User Sudmong
by
6.3k points